2014
DOI: 10.1088/0963-0252/23/5/054016
|View full text |Cite
|
Sign up to set email alerts
|

Features of a near-cathode region in a gliding arc discharge in air flow

Abstract: This paper describes the results of the investigation of a low-current atmospheric-pressure discharge in air flow with electrode geometry typical of the so-called gliding arc. At a current of fractions of an ampere the discharge burns in a regime of normal glow rather than in an arc regime and the area of the negative glow plasma smoothly moves over the cathode surface under the effect of gas flow. At the background of the glow discharge, occasional creation of a spark cathode spot can occur. Then the discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…The core plasma column has a much higher temperature than the surrounding region around it, and thus an overestimation of the size of the plasma column could underestimate the translational temperature of the plasma column and its reduced electric field strength. Korolev and associates [31] found that the reduced electric field strength of a low-current gliding arc discharge was about 30 Td with a gas temperature of about 4100 K in the plasma column. …”
Section: Electron Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The core plasma column has a much higher temperature than the surrounding region around it, and thus an overestimation of the size of the plasma column could underestimate the translational temperature of the plasma column and its reduced electric field strength. Korolev and associates [31] found that the reduced electric field strength of a low-current gliding arc discharge was about 30 Td with a gas temperature of about 4100 K in the plasma column. …”
Section: Electron Temperaturementioning
confidence: 99%
“…It should be noted that there exits a significant voltage drop across the sheath region of the glow-type discharge. The voltage drop of a low-current gliding arc discharge operated at a glow-type regime was reported to be about 300 V [31,33]. In this work, a voltage drop of 300 V is taken into consideration when calculating the reduced electric field strength using Eq.…”
Section: Translational Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Such gliding arc discharges have been widely applied to pollution control, 7-11 surface treatment, 1,12 sterilization, 13 and combustion enhancement. 14 Extensive studies have been performed on the dynamics, [15][16][17][18] physical characteristics, [19][20][21][22][23][24][25][26][27][28] and chemical mechanisms [29][30][31] involved in gliding arc discharges. Phenomenological models 21,[32][33][34] were developed to explain the discharge behavior based on accurate measurements of several important parameters, including the slip velocityṼ S (it stands for the relative velocity between the plasma columnṼ C and the gas flowṼ F , and its magnitude is jṼ S j ¼ jṼ C ÀṼ F j), and the length of the plasma column.…”
mentioning
confidence: 99%
“…Kono and Iwamoto (2004) Gliding arc 3 60 Korolev et al (2014), Wu et al (2015) NEAPP -320 Iwasaki et al (2008) LIBS 100 800 Nedanovska et al (2011) In 2006, Fridman reported replacing one of the electrodes in a DBD with a biological object with high capacitance and using it as a floating electrode, as shown in Fig. 8.…”
Section: Plasma Sourcesmentioning
confidence: 99%